2021
DOI: 10.3390/v13020250
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus and Peri-Implantitis: A Systematic Review and Meta-Analysis

Abstract: The exponential growth in the use of dental implants in the last decades has been accompanied by an increase in the prevalence of peri-implant disease. It appears that viruses may have pathogenic potential for the development of this pathology. The objective of this systematic review is to study the possible association between the presence of Epstein–Barr virus and the development of peri-implantitis. An electronic search was conducted in PubMed/MEDLINE, Scielo and Embase databases for cross-sectional and cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, it appears that bacteria genes encoding resistance to metronidazole are less frequent in peri-implant tissues than those that encode resistance to beta-lactams [34]. In addition, bacteria related to dental implant failure [35] and peri-implantitis [36,37] can be variable and complex, but it consists in part of Gram-negative anaerobic species against which metronidazole is the antibiotic of choice [38,39]. For these reasons, it would be interesting to investigate the effectiveness of metronidazole in reducing dental implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that bacteria genes encoding resistance to metronidazole are less frequent in peri-implant tissues than those that encode resistance to beta-lactams [34]. In addition, bacteria related to dental implant failure [35] and peri-implantitis [36,37] can be variable and complex, but it consists in part of Gram-negative anaerobic species against which metronidazole is the antibiotic of choice [38,39]. For these reasons, it would be interesting to investigate the effectiveness of metronidazole in reducing dental implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein Barr Virus is known to cause Systemic Lupus Erythematosus. A systematic review (Roca-Millan et al, 2021) found no statistically significant difference between peri-implantitis and healthy patients with respect to EBV presence in peri-implant sulcus. A systematic review (Sgolastra et al, 2015) revealed that patients with periodontitis has a moderate risk for peri-implantitis and higher risk for implant loss in contrast to our retrospective study patients with periodontitis may pose a moderate risk to periimplantitis when compared to SLE and RA patients but not significantly higher risk when compared to healthy patients.…”
Section: Discussionmentioning
confidence: 97%